GENETIC DIVERSITY IN EIGHT PURE BREEDS AND URBAN FORM OF DOMESTIC PIGEON (COLUMBA LIVIA VAR. DOMESTICA) BASED ON SEVEN MICROSATELLITE LOCI - A. Biała; A. Dybus; E. Pawlina; W. S. Proskura (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to examine if there was a gene flow between different breeds and forms of domestic pigeon. Seven pigeon microsatellite markers were used to examine the genetic variability and relationships among eight pure breeds and urban form of domestic pigeon. In total, 7 microsatellite loci were genotyped in 364 individuals giving a total of 122 alleles. This study is the first to report microsatellite analysis in Wroclaw Meat pigeons. The inbreeding coefficient showed a departure from random mating, which is expected for a breeding flock and the artificial selection of breeding pairs. Interestingly, the German Nun breed showed a mixed genetic heritage derived from the Fantails, Kassel Tumblers and Vienna highflier breeds. Urban pigeons appeared to form a separate population with completely different features than the rest of those analysed and should probably be considered as a crossbreed population.In conclusion all breeds and diverse morphological forms of Columbalivia should be considered as a result of extraordinary phenotypic plasticity of this species rather than as outcome of total isolationof subpopulations.
Keywords: Columba livia; microsatellite DNA; pigeon breeds; population structure